2003
DOI: 10.1046/j.1365-2141.2003.04633.x
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell involvement is predictive of response to induction chemotherapy in paediatric acute myeloid leukaemia

Abstract: Summary. In acute myeloid leukaemia (AML), involvement of early progenitor cells may predict poor response to induction chemotherapy. We evaluated the involvement of early progenitor cells in two AML subtypes with a favourable prognosis [t(8;21) and t(15;17)], and a subtype with poor prognosis (monosomy 7). CD34 + CD33 ) cells were isolated by fluorescence-activated cell sorting, grown in liquid medium followed by culture in semi-solid medium, and the colonies that were formed were analysed for the identifiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For example, APL, a disease that is limited to a mature precursor population, has excellent clinical outcome. 3,26,27 Moreover, studies in monosomy 7 (Ϫ7) AML demonstrate that response to induction chemotherapy correlates with extent of early progenitor cell involvement, with patients demonstrating the cytogenetic abnormality in less-mature CD34 ϩ /CD33 Ϫ hematopoietic progenitors having worse response to induction therapy than patients in which Ϫ7 is limited to a more differentiated population. 3 Our data further support this concept, suggesting that FLT3/ITD detection is heterogeneous in CD34 ϩ /CD33 Ϫ myeloid progenitors and that disease involvement of this precursor population may correlate with poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, APL, a disease that is limited to a mature precursor population, has excellent clinical outcome. 3,26,27 Moreover, studies in monosomy 7 (Ϫ7) AML demonstrate that response to induction chemotherapy correlates with extent of early progenitor cell involvement, with patients demonstrating the cytogenetic abnormality in less-mature CD34 ϩ /CD33 Ϫ hematopoietic progenitors having worse response to induction therapy than patients in which Ϫ7 is limited to a more differentiated population. 3 Our data further support this concept, suggesting that FLT3/ITD detection is heterogeneous in CD34 ϩ /CD33 Ϫ myeloid progenitors and that disease involvement of this precursor population may correlate with poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,24 Alternatively, disease may evolve from a committed myeloid progenitor, as is thought to be the case with acute promyelocytic leukemia (APL). 3,25,26 Ultimately, the maturational stage at which frank leukemic transformation occurs may dictate clinical response. For example, APL, a disease that is limited to a mature precursor population, has excellent clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro work suggested that the maturational stage at which leukemic transformation occurs may dictate clinical response, with more favorable outcomes seen when disease is derived from a more committed myeloid progenitor. [22][23][24][25] If this is the case, then those patients with CD33 low/absent blast expression may be more sensitive to conventional chemotherapy and potentially GO, assuming that CD33 expression, if present, is sufficient for GO targeting.…”
Section: Discussionmentioning
confidence: 99%
“…-cells harboring the monosomy 7 abnormality did not respond well to induction therapy (8). Future detailed studies should determine the extent of committed progenitor cells as the cell of origin in human AML, and if the cell of origin influences outcome.…”
Section: Cd33mentioning
confidence: 99%